2015
DOI: 10.1088/1748-3190/10/2/026002
|View full text |Cite
|
Sign up to set email alerts
|

A small-scale hyperacute compound eye featuring active eye tremor: application to visual stabilization, target tracking, and short-range odometry

Abstract: In this study, a miniature artificial compound eye (15 mm in diameter) called the curved artificial compound eye (CurvACE) was endowed for the first time with hyperacuity, using similar micro-movements to those occurring in the fly's compound eye. A periodic micro-scanning movement of only a few degrees enables the vibrating compound eye to locate contrasting objects with a 40-fold greater resolution than that imposed by the interommatidial angle. In this study, we developed a new algorithm merging the output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…However, to be able to track more complex targets, in natural environements, with texture and and objects, this simple eye could be replace by another minimalistic bio-inspired eye [37]. Indeed, it was proven that such an eye was able to perform visual odometry tasks, and could also be used to track a target moving over a textured background [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to be able to track more complex targets, in natural environements, with texture and and objects, this simple eye could be replace by another minimalistic bio-inspired eye [37]. Indeed, it was proven that such an eye was able to perform visual odometry tasks, and could also be used to track a target moving over a textured background [30].…”
Section: Discussionmentioning
confidence: 99%
“…The focallength of each lens was adjusted to implement a Gaussian angular sensitivity ∆ρ of 3.7°for each pixel, and an inter-pixel angle ∆φ of approximatively 3.9°(see figure 2). As described in (see [24], [28], [30]), we need an active vibration system Fig. 1.…”
Section: A New Gimbal Visual Systemmentioning
confidence: 99%
“…However, several authors have integrated micro movements of this kind into their artificial visual sensors, and the results obtained have shown that they were able to locate a contrasting target with much greater accuracy (up to 700-fold) than that achieved using optical systems alone [22,57]. Thanks to this hyperacuity, it was recently established using a biorobotic approach that a contrasting moving target (moving hands) could be located on a textured background and the distance travelled by a micro robot flying above a textured plane could be measured by processing the visual signals conveyed by the 40 ommatidia in a vibrating artificial compound eye [8]. The presence of hyperacuity has not yet been clearly determined in insects, but a highly counter-intuitive principle in which coarse and blurry vision (due to the Gaussian angular sensitivities of the photoreceptors) is combined with vibration seems to be able to give a more accurate perception of the world.…”
Section: Fly-inspired Hyperacute Sensormentioning
confidence: 99%
“…Optic flow is a popular technique for the real-time stabilisation and control of small-size rotorcraft [23,31,45,[94][95][96][97].…”
Section: Control Of Uas Hover Through Snapshot Matchingmentioning
confidence: 99%